Pareto analysis in bulldozer’s failures and stoppages risk management - Spasojević-Brkić, Vesna K; Perišić, Martina; Veljković, Zorica; Misita, Mirjana; Damjanović, Milanko (Industrija, 2023)
Research related to risk management of failures and stoppages in the operation of bulldozer is very limited, so this topic needs more attention.  This study aims to identify all possible causes for bulldozer failures and stoppages before highlighting the most significant ones. Descriptive statistics are provided, followed by a scatterplot for the dissipation diagram between hazard rate and bulldozer failure and stoppages, and histograms of hazard rate and failures and stoppages for bulldozers. Then, for three categories, a Pareto analysis was performed on failures and stoppages frequency, time spent in failures and stoppages, and failures and stoppages risk level. The Pareto analysis revealed that the most important failures and stoppages in all three categories were caused by heating repair, oil change, bulldozer cleaning, tonsil adjustment, filter replacement, hose replacement and screw replacement. The step towards “maintenance free factories” should include planning of identified activities in work breaks as preventive rather than corrective activities.
Keywords: Pareto analysis, bulldozer, failure type, failure frequence, failure time, failure risk